In vivo TSPO imaging in patients with multiple sclerosis: a brain PET study with [(18)F]FEDAA1106 - Takano, Akihiro (Springer, 2013)
BACKGROUND: The activation of microglia, in general, and the upregulation of the translocator protein (18 kDa) (TSPO) system, in particular, are key features of neuroinflammation, of which the in vivo visualization and quantitative assessment are still challenging due to the lack of appropriate molecular imaging biomarkers. Recent positron emission tomography (PET) studies using TSPO radioligands such as [(11)C]PK11195 and [(11)C]PBR28 have indicated the usefulness of these PET biomarkers in patients with neuroinflammatory diseases, including multiple sclerosis (MS). [(18)F]FEDAA1106 is a recently developed PET radioligand for the in vivo quantification of TSPO. In the present study, we aimed at investigating the diagnostic usefulness of [(18)F]FEDAA1106 in patients with MS. METHODS: Nine patients (three on the interferon beta therapy and six without immunomodulatory therapy; seven females/two males; age 34.2 ± 9.1 years old) with relapsing-remitting MS in acute relapse and with gadolinium (Gd)-enhancing lesion(s) in the magnetic resonance imaging (MRI) scans and five healthy controls (four females/one male, age 38.0 ± 9.7 years old) were investigated in this study. Genetic information about the TSPO binding could not be obtained because knowledge about the importance of genetic background for TSPO binding was not available at the time the study was performed. Dynamic PET measurements were performed using an ECAT EXACT HR system (CTI/Siemens, Knoxville, TN, USA) for a total of 150 min, with a 30-min break after the injection of 153.4 ± 10.2 MBq of [(18)F]FEDAA1106. Metabolite-corrected arterial plasma samples were used to calculate the input function. PET data were analyzed in the following ways: (1) region-of-interest analysis for cortical and subcortical regions was performed using a two-tissue compartment kinetic model in order to estimate binding potentials (BP(ND)) and distribution volume (VT), (2) the feasibility of the estimation of BP(ND) and VT was investigated for MS lesions, and (3) VT parametric images by a Logan plot and standard uptake value (SUV) images were visually compared with the corresponding MRI, focusing on MRI-identified MS lesions. RESULTS: There were no significant differences in the BP(ND) or VT values between patients with MS and healthy controls. Robust BP(ND) and VT values could not be obtained for most MS lesions due to noisy time-activity curves. Visual inspection of VT and SUV images in all nine patients did not reveal high uptake of the radioligand inside and beyond MRI-identified active MS lesions with the exception of one Gd-enhanced MS lesion in the whole patient population. CONCLUSIONS: In our study, [(18)F]FEDAA1106 as a PET radioligand could neither differentiate patients with MS from healthy controls nor detect active plaques in the brain of MS patients. Stratification with respect to genetics and binder status might help to uncover the differences between the groups, which could not be detected here. TRIAL REGISTRATION: ClinicalTrials.gov, NCT01031199